Atomistic investigation of mechanical properties of metallic glass nanocomposites. (21st October 2020) - Zhou, Xiaoling; Wang, Longqi; Chen, Changqing
Abstract: In this paper, tensile deformation of metallic glass (MG) nanocomposites which consist of cellular MG matrix and columnar grains are studied by the molecular dynamic simulations. The size effects of the ligament thickness and the grain size on the yield strength and plasticity are elucidated. It is found that the ratio of the grain size to the ligament thickness ( d / s ) has a great influence on the plastic deformation. Two typical deformation mechanisms are further investigated. In the composite models with large d / s, grain boundaries motion and voids formation are the main mechanisms. When d / s decreases to 6, the grains can not only promote multiple shear bands formation but also impede the main shear band propagation. As a result, large plastic plateau appears in the stress–strain curve. These results are helpful to optimize the mechanical properties of MG composites.